2013
DOI: 10.1038/modpathol.2012.168
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry with a mutation-specific monoclonal antibody as a screening tool for the BRAFV600E mutational status in primary cutaneous malignant melanoma

Abstract: The V600E mutation of BRAF has emerged as both an effective biomarker and therapeutic target for select benign and malignant cutaneous and non-cutaneous human tumors and is typically determined using DNAbased techniques that include allele-specific PCR and direct DNA sequencing. Recently however, the development of new antibodies directed against the V600E protein has opened the door for an easier and more efficient strategy for identifying this mutation. Our present aim was to determine the efficacy of one su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 28 publications
4
45
1
Order By: Relevance
“…Our findings show that in colorectal carcinoma, VE1 IHC is not a reliable method for determining the BRAF V600E mutational status. In contrast, our results in melanoma and papillary thyroid carcinoma are in keeping with previously published data showing excellent concordance between molecular analysis and VE1 IHC (36)(37)(38)(39)(40)(41).…”
Section: Discussioncontrasting
confidence: 54%
“…Our findings show that in colorectal carcinoma, VE1 IHC is not a reliable method for determining the BRAF V600E mutational status. In contrast, our results in melanoma and papillary thyroid carcinoma are in keeping with previously published data showing excellent concordance between molecular analysis and VE1 IHC (36)(37)(38)(39)(40)(41).…”
Section: Discussioncontrasting
confidence: 54%
“…Previous immunohistochemical analyses using BRAFV600E antibody have shown that intratumoral heterogeneity of BRAF mutation is not generally observed [23][24][25] and up to 100% concordance between matched primary and metastatic melanomas has been reported. 24 These results support the routine use of immunohistochemistry with the anti-BRAFV600E antibody as an ancillary screening tool to assess the BRAFV600E mutation status in melanoma patients 26 for treatment planning.…”
Section: Discussionmentioning
confidence: 61%
“…This antibody provides highly sensitive (97–100%) and specific (97–100%) insight into the BRAF V600E mutation status of patients with melanoma [712]. Homogeneous BRAF V600E IHC expression in melanoma highly correlates with the presence of BRAF V600E mutation when compared with sequencing methods as the gold standard.…”
Section: Introductionmentioning
confidence: 99%